Marketing Strategy for Ikan Bakar Jimbaran, Yogyakarta - Sawitri, Ajeng; Inggriantara, Alibasjah (The Indonesian Journal of Business Administration, 2015)
Abstract.Ikan Bakar Jimbaran was a pioneer of fresh seafood premium restaurant in Yogyakarta with Baliâ€™s ambience. In the first 5 years, they had a good sales performance. However, financial data shows decrease on sales and number of customers in this last 3 years. The rising of new hotels, guest houses, and restaurants in Yogyakarta is suspected as the cause of decreasing sales. Moreover, Ikan Bakar Jimbaran, which is lack of marketing activities, is looked dissapear in the midst of happening culinary reports in social media. They do not apply new marketing methods and only hold on to the strength of word-of-mouth. The absence of officer who should handle all online marketing activities could be one of the causes. To solve the business issue, analysis of external and internal environment is needed. External factor analysis consists of PEST and 5 FORCES; while STP and 7P are used to analyze internal factor. In addition, the result of interview with the manager and customers of Ikan Bakar Jimbaran becomes one of sources in listing SWOT. From SWOT result, TOWS matrix is utilized to generate alternative marketing strategies for Ikan Bakar Jimbaran. There are 14 proposed marketing strategies which are formulated into 7P and the implementation was described in action program scheduled for five years ahead. To sum up, Ikan Bakar Jimbaran need to apply new marketing methods rather than depend on word-of-mouth. They may start taking advantage of all opportunities that Internet presents. Thus, a social media account officer who will handle all marketing activities related to the Internet should be hired as one of strategies to overcome the problem.Keywords: Seafood Restaurant, Decrease on Sales, Marketing Strategy.Â